Venous thromboembolism risk among pediatric patients with traumatic brain injury: a nationwide study of 44,128 patients - Hoffmann, Ildiko; Lewis, Erin R.; Marini, Corrado; McNelis, John; Viswanathan, Shankar; Posti, Jussi P.; Lieb, David A.; Wilson, Michael (Journal of neurosurgery. Pediatrics, 2023)
OBJECTIVE Venous thromboembolism (VTE) chemoprophylaxis in pediatric patients with traumatic brain injury (TBI) requires balancing the risk of progression of intracranial bleeding versus the risk of VTE. The identification of VTE risk factors requires analysis of a very large data set. This case-control study aimed to identify VTE risk factors in pediatric patients with TBI in order to develop a TBI-specific association model that can be used for VTE risk stratification in this population. METHODS The study included patients (aged 1-17 years) from the 2013-2019 US National Trauma Data Bank who were admitted for TBI in order to identify risk factors for VTE. Stepwise logistic regression was used to develop an association model. RESULTS Of 44,128 study participants, 257 (0.58%) developed VTE. Risk factors associated with VTE included age (OR 1.045, 95% CI 1.010-1.080), body mass index (OR 1.034, 95% CI 1.013-1.055), Injury Severity Score (OR 1.049, 95% CI 1.039-1.059), blood product administration (OR 1.436, 95% CI 1.008-2.046), presence of a central venous catheter (OR 3.333, 95% CI 2.431-4.571), and development of ventilator-associated pneumonia (OR 3.650, 95% CI 2.469-5.396). Based on this model, the predicted VTE risk in pediatric patients with TBI ranged from 0% to 16.8%. CONCLUSIONS A model that includes age, body mass index, Injury Severity Score, blood transfusion, use of a central venous catheter, and ventilator-associated pneumonia can help to risk stratify pediatric patients with TBI from the standpoint of implementation of VTE chemoprophylaxis.